2021
DOI: 10.3390/jof7080626
|View full text |Cite
|
Sign up to set email alerts
|

The PPIP5K Family Member Asp1 Controls Inorganic Polyphosphate Metabolism in S. pombe

Abstract: Inorganic polyphosphate (polyP) which is ubiquitously present in both prokaryotic and eukaryotic cells, consists of up to hundreds of orthophosphate residues linked by phosphoanhydride bonds. The biological role of this polymer is manifold and diverse and in fungi ranges from cell cycle control, phosphate homeostasis and virulence to post-translational protein modification. Control of polyP metabolism has been studied extensively in the budding yeast Saccharomyces cerevisiae. In this yeast, a specific class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Pascual-Ortiz et al reported recently that cellular polyphosphate levels correlate with the levels of IP8 synthesized by Asp1 ( 37 ). In agreement with their findings, we see that the polyphosphate content of asp1 Δ and asp1-D333A cells, which fail to synthesize IP8 and have elevated levels of IP7, is clearly reduced compared to that of the wild-type, albeit not depleted completely as in vtc4 Δ cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pascual-Ortiz et al reported recently that cellular polyphosphate levels correlate with the levels of IP8 synthesized by Asp1 ( 37 ). In agreement with their findings, we see that the polyphosphate content of asp1 Δ and asp1-D333A cells, which fail to synthesize IP8 and have elevated levels of IP7, is clearly reduced compared to that of the wild-type, albeit not depleted completely as in vtc4 Δ cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We thereby found that the Gde1 glycerophosphodiesterase, Vtc4 polyphosphate polymerase, and Spx1 RING ubiquitin ligase were necessary for IPP toxicosis. It is established that IPPs bound to the SPX domain are potent allosteric activators of the polyphosphate synthesis by the yeast VTC complex ( 34 ) and that fission yeast polyphosphate levels increase in IPP pyrophosphatase-defective asp1-H397A cells that have elevated levels of IP8 ( 37 ). We envision that IPP binding to the SPX domains of Gde1 and Spx1 regulates their enzymatic activities as well.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of fis sion yeast strains bearing kinase-defective asp1 mutant alleles ( asp1 Δ or asp1-D333A ) that have no intracellular IP 8 , and of cells with a pyrophosphatase-defective asp1-H397A allele that have elevated levels of IP 8 , implicate IP 8 in a variety of physiological events ( 9 , 10 , 19 , 30 32 ). At the transcriptional level, IP 8 governs expression of the fission yeast phosphate regulon, such that Pho1 acid phosphatase is hyper-repressed in cells lacking IP 8 and overexpressed in cells with elevated IP 8 (19).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present work draw attention to the participation of diphosphoinositol polyphosphate in stress response, and the necessity for the further analysis of inter-relationships between polyphosphates and these signaling molecules. These inter-relationships are quite complex and variable among microorganism species [38,39].…”
Section: Discussionmentioning
confidence: 99%